Systematic Review on The Role of Gender and Language Learning Strategies (LLS) - Ibrahim, NoorAileen; Taharuddin, Nurul Shima; Yusof, Ahmad Muhyiddin; Nazri, Haslinda Md.; Sedhu, Daljeet Singh; Azamri, Nurul Munirah; Mutalib, Halimatun Saadiah Abd; Idris, Sheema Liza; Zakaria, Mohd Radhuan Arif (Journal of Accounting, Business and Management (JABM), 2024)
le to master the language. These struggles generally encompass internal as well as external challenges. Some examples of internal factors comprise low motivation, interest, and focus besides a poor attitude towards the target language in question. Meanwhile, some external factors normally include ineffective and inappropriate teaching and learning (T & L) methods, an unsupportive classroom environment, and a lack of support and encouragement from family and friends. This study aims to determine the role of gender in English as a second language (ESL) learners’ use of language learning strategies (LLS). Online databases such as Google Scholar, Education Resources Information Centre (ERIC), Scopus, and ProQuest were used to identify the relevant literature. Online searches conducted from 2010 and 2022 revealed 197 studies on the topic. The systematic literature review method was employed for this study. However, only 23 kinds of literature out of 197 were selected for inclusion according to specific criteria outlined by the research purpose mentioned above. Based on the results it was found that gender does play a significant role in the ESL learners' use of LLS due to several factors such as aptitude, emotional and communicative motivation, and positive attitude. Moreover, individual personality, social differences, physiological functioning, and home environment can influence the LLS used by ESL learners. It was found that the preferred LLS includes cognitive, compensation, and affective strategies.